RESPON PERTUMBUHAN TANAMAN SORGUM (Sorghum bicolor. L.) TERHADAP TINGKAT KELENGASAN DAN DOSIS PUPUK KANDANG SAPI YANG BERBEDA - Amiruddin, Amiruddin; Hasanah, Uswah; Samudin, Sakka (AGROTEKBIS, 2017)
This study aims to investigate the response of the sorghum growth to the level of humidity and dosage of different cow manure. This study was conducted using a randomized block design (RBD) consisted of two factors and three replications. The first factor is the provision of water consists 25% of field capacity, 50% of field capacity, 75% and 100% of field capacity. The second factor is without cow manure and cow manure 40 ton/ ha and 60 ton/ha. It obtained 4x3 = 12 treatments repeated 3 times terefore there is a 12 x 3 = 36 experiments. Variables include observation of plant height, stem diameter, number of leaves, leaf greenness, leaf area, plant fresh weight and dry weight of plants. The results showed that there was no interaction between the water content and cow manure on the growth of sorghum. Cow manure had no effect on all components of sorghum growth whereas the water content treatment very significant effect on the growth of sorghum, plant fresh weight and dry weight of plants.Â Keywords: Cow manure, growth, sorghum, water content.